Cinta dan Perempuan: Analisis Wacana Berbasis Korpus Lagu Dangdut dan Pop Indonesia - Salsabila, Jihan (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2025)
This study aims to analyze the representation of women depicts in Indonesian Dangdut and Pop song lyrics that raise the theme of love. To see patterns of representation in the selection and use of words in song lyrics, the framework of representation theory and cultural feminism is used. The results of research using the corpus-assisted discourse studies (CADS) method show that the representation of women still leads to physical objectification, women are the subject of emotional experiences, and women are seen as subordinate figures in romantic relationships. Using the framework of representation theory and cultural feminism to analyze the findings, it is seen that there is complexity and contradiction in the representation of women. Although there have been efforts to represent them positively, dangdut mostly represent women as the subjects of the bitterness of love. While pop songs emphasize women more as objects of beauty. Both genre still reinforce gender stereotypes. Through this study, it is clear that changes need to be made to encourage a more empowering representation of women in popular culture.it can be concluded that changes need to be made to encourage a more empowering representation of women in popular culture.